Serial measurements of Paraoxonase-1 (PON-1) activity in horses with experimentally induced endotoxemia - Scavone, Donatella; Sgorbini, Micaela; Borges, Alexandre S. [UNESP]; Oliveira-Filho, José P. [UNESP]; Vitale, Valentina; Paltrinieri, Saverio (Springer Nature, 2020)
Background: Paraoxonase-1 (PON-1) is an antioxidant enzyme, whose activity decreases during the acute phase response in many species. Little is known about PON-1 and its role as a negative acute phase protein during septic inflammation in horses, but promising findings about its utility in diagnosing SIRS and predicting the outcome in diseased horses, were recently highlighted. The objective of the study was to investigate the behaviour of PON-1 in horses after experimentally induced endotoxemia. To this aim, PON-1 activity was measured on 66 plasma samples collected from six clinically healthy mares, previously included in another study, before and at multiple time points between 12 and 240 h after intravenous infusion of Escherichia coli O55:B5 lipopolysaccharide (LPS). Results: Compared with baseline values, a progressive transient decrease of PON-1 activity was observed starting from 24 h post-infusion, with lowest values observed between 3 to 7 days post-infusion, followed by a normalisation to pre-infusion levels the tenth day. Conclusions: The results of this study suggest that measurement and monitoring of PON-1 activity might be useful to evaluate progression and recovery from endotoxemia in horses. Further studies in horses with naturally occurring sepsis are warranted.
Keywords: Equine; Inflammation; Oxidative stress